Uma abordagem temporal para identificação precoce de estudantes de graduação a distância com risco de evasão utilizando técnicas de mineração de dados - Santos, Ramon Nóbrega dos (2015)
Through the use of data mining techniques, more usually the classification algorithms, it is possible to implement predictive models that are able to early identify a student in risk of dropout. Several studies used data obtained from a Virtual Learning Environment (VLE) to implement predictive performance models in a discipline of a course. However, any study was carried out aimed at developing a model for dropout prediction, to distance graduation courses of longer duration, which integrates works that carry out performance prediction based on a VLE, allowing an early prediction during the first semester and throughout the others semesters. Thus, this work proposes a dropout identification approach for distance graduation courses that use the Rule-Based Classification technique to firstly identify the disciplines and grades limits that have higher influence on dropout, so that the predictive models for performance in a VLE can be used regarding the dropout detection of students along the whole distance graduation course. Experiments were carried out using four rulebased classification algorithms: JRip, OneR, PART and Ridor. Considering the use of this temporal approach, it was possible to prove the advantages of this approach, once better accuracies were obtained along the semesters and important rules were discovered to early identify students in risk of dropout. Among the applied algorithms, JRip and PART obtained the best predictive results with average accuracy of 81% at the end of first semester. Furthermore, considering our proposed partition methodology, where attributes of the predictive models are incrementally applied, it was possible to discovery rules potentially useful to dropout prevention.